PARADIGMA BARU PENYELESAIAN SENGKETA MEDIS DI INDONESIA PASCA UU KESEHATAN 2023: KAJIAN ALTERNATIF DAN LITIGASI - Gunawan Widjaja; Andreas Harry (Jurnal Kesehatan, 2025)
Law No. 17 of 2023 on Health introduces a new paradigm in medical dispute resolution in Indonesia through the strengthening of the Alternative Dispute Resolution (ADR) mechanism as the primary step before resorting to litigation. This change is intended to ensure faster, cheaper, confidential, and fair justice for both patients and medical personnel while preventing the criminalisation of medical actions that are in accordance with standards. This study aims to analyse the concept and implementation of the new paradigm regulated in the 2023 Health Law, including the effectiveness of ADR and its relationship with civil and criminal litigation. Using a normative legal research method and a legislative and conceptual approach, this study found that while APS has great potential to reduce the escalation of medical conflicts, its success heavily depends on the readiness of implementing institutions, the understanding of all parties, and the harmonisation of subsidiary regulations. On the other hand, litigation remains the final resolution pathway if ADR fails, but its implementation needs to be aligned with the spirit of restorative justice as envisioned in national health law reform.